The impact of bank’s diversity and inclusion index on profitability: evidence from Indonesia and Malaysia - Tumewang, Yunice Karina; Fakhrunnas, Faaza; Ardiami, Kinanthi Putri (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This study aims to investigate the effects of the Diversity and Inclusion Rating (DIR) score on profitability, comparing conventional and Islamic banks. Employing the available data on DIP and ESG (Environmental, Social, and Governance) scores from the Refinitiv database, this study took a dataset of 100 firm-year observations which consists of both conventional and Islamic banks in Indonesia and Malaysia. We conducted a random-effect regression model with the inclusion of some appropriate control variables as well as year and country dummies. The findings of this study prove that there is a positive and significant association between DIR and both profitability ratios of ROA and ROE. Meanwhile, for Islamic banks, DIR is negatively related to ROA and ROE for several reasons explained in this study, including the partial misalignment of conventional Diversity & Inclusion proxy with Sharia principles.